An unusual complication of melaena on a warfarinised patient following a routine dental extraction: a case report. (24th February 2014) - Campbell, N.; Patel, K.
Abstract: A case report of a 79‐year‐old man who was on warfarin for atrial fibrillation and developed melaena following a dental extraction is presented here. To give the reader an appreciation of: Warfarin as an anticoagulant Complications following dental extractions of warfarinised patients A new complication, faecal blood, following a dental extraction